The Classroom Interaction Patterns among Lecturer and Students of Pronunciation Class in English Department - Yeyisha Shellayukti (BRILIANT: Jurnal Riset dan Konseptual, 2020)
This study was aimed to investigate classroom interaction with regard to the patterns of classroom interaction, speech functions and code-mixing and code switching among the lecturer and students in Pronunciation class of UNNES as well as the implications. The data were collected from the classroom observation and the recording of teaching and learning process. The method carried out in this study were using Walsh (2012) about Classroom Interaction Analysis, Eggins and Slade (1997) about Speech Functions and code-mixing and code-switching (Hymes, 1974). The descriptive qualitative approach was used to carry out this study. The result of the study showed the patterns of interaction among lecturer and students in pronunciation class of English Department in UNNES was quite dynamic, since the patterns of classroom interaction shift during the learning process from IRF and IRE vice versa. Since, the materials are mostly about pronouncing the words, the students never asked to work in a group to do a discussion. The speech functions also showed variety of moves carried out by the lecturer and students. The speech functions carried out by the lecturer are always followed by the students. Hence, the moves almost have the same portions among lecturer and students. It indicated that the process of exchange between lecturer and students was well maintained. Meanwhile, the lecturer used so many code-switching and code-mixing in the teaching and learning process which represents the efforts to abridge the students understanding in mastering the materials.